Femtosecond laser-assisted corneal intrastromal negative meniscus lenticule implantation with accelerated collagen crosslinking (FILAC) in advanced keratoconus in Indian eyes: A prospective interventional study - Rajesh Sinha; Shahnaz Anjum; Kartikeya Gupta; Tushar Agarwal; Namrata Sharma; Sridevi Nair; Shrishti Kapoor; Jeewan S Titiyal (Indian Journal of Ophthalmology)
Purpose: To study the outcomes of femtosecond laser-assisted intrastromal negative meniscus lenticule implantation with accelerated corneal collagen crosslinking (FILAC) in advanced keratoconus. Methods: A prospective, interventional study evaluated the outcomes of FILAC in eyes with progressive keratoconus of Amsler-Krumeich stage 4 with thinnest pachymetry of 320–400 microns. A total of 10 eyes of 10 patients were enrolled. A negative meniscus allogenic stromal lenticule of 8.5 mm diameter was implanted into a corneal pocket created by a femtosecond laser at 150 microns depth and simultaneous accelerated corneal collagen crosslinking (CXL). Outcomes assessed 12 months after the procedure included uncorrected distance visual acuity (UDVA) and best-corrected visual acuity (BCVA), subjective refraction, and corneal topography changes. Results: Mean UDVA improved from baseline to 12 months follow-up (1.43 ± 0.39 vs. 1.32 ± 0.31 logMAR, P = 0.49). Four patients did not accept contact lenses preoperatively, whereas all patients were successfully fitted with semi-scleral contact lenses postoperatively with a mean BCVA of 0.47 ± 0.14 logMAR at 12 months. Mean corneal topographic values showed improvement from baseline to 12 months follow-up: K1 (58.44 ± 5.59 to 55.57 ± 5.68), K2 (63.35 ± 6.86 to 59.35 ± 7.1), Kmax (71.07 ± 7.95 to 66.29 ± 7.54) and astigmatism (4.89 ± 3.35 to 3.88 ± 2.35) (P > 0.05). The mean thinnest pachymetry improved significantly from baseline to 12 months follow-up (354.9 ± 28.52 vs. 462.5 ± 36.30 microns, P = 0.0001). There was a non-significant improvement in subjective refraction and aberrometry. Conclusion: This technique effectively halts disease progression and improves visual outcomes in advanced keratoconus.